Kesiapan Sarana Transportasi Laut Dalam Pengembangan Industri Kepariwisataan di Kepulauan Seribu - Karana, Sjafril (Warta Penelitian Perhubungan, 2011)
Kepulauan Seribu can be accessed only by sea vessels from Muara Angke Port and Marina Jaya Ancol north Jakarta. There are two type of ships have been services, traditional vessels and the other is speed boats. The traditional vessels are very dominan to be used eventlwugh they are very danger to be operated as a passenger vessels because they do not fulfilled the requirements especially in safeh; equipment, nevertheless they are still in operation. During its operation, vessels are loaded with passengers exceeding the permitted capacity, of course this condition is very dangerous when big wave come. In relation with to tourism activihj, the bad operational condition of the traditional vessels will cause number of tourists who visit the Kepulauan Seribu decline. T71is research was conducted based on literature study supported by the data and information from various sources. The analysis showed that the bad operation condition vessels was caused by weak law enforcement, besides that there is also a factor of lacking of understanding about the safety of ships in good voyage by the crew, and vessel operators. To improve the flaw of tourist visits to the Kepulauan Seribu, more effort is needed, mainly reconstruction of traditional vessels because it relates to the safety of human life at sea, besides that it should also imp rave understanding of various aspects of the tourism industry.Keywords : vessel, tau rism industry